Empirical Analysis of Urban Community Social Vulnerability in Hilly Areas of Kajang - Nor Diana Mohd Idris; Zulkepli Nurul Atikah (E3S Web of Conferences)
The occurrence of landslides in Malaysia have increased significantly by year due to climate and development activities happening in Malaysia. The increasing phenomenon of landslide events in Malaysia especially in the urbanised area has greatly impacted the community living in those affected areas. Therefore, to determine the social vulnerability of the community living in the hilly areas of Kajang, the study assessed the social vulnerability index by using Principal Component Analysis (PCA). Seventeen variables were selected to determine the index including age, health, education, single-parent household, vehicle ownership, housing, income, unemployment, and elevation. Using stratified sampling, 200 respondents from the areas of Kajang Mewah Hilly and Kajang Utama Hilly were selected. Overall, the study shows that the people living in Kajang Mewah Hilly area is more vulnerable compared to Kajang Utama Hilly area if landslides happen here. Therefore, there is a need to increase the resilience of the community to disaster event as well as increase the mitigation efforts by the local authorities.